Outcomes from the Delphi process of the Thoracic Robotic Curriculum Development Committee - Veronesi, Giulia; Dorn, Patrick; Dunning, Joel; Cardillo, Giuseppe; Schmid, Ralph A; Collins, Justin; Baste, Jean-Marc; Limmer, Stefan; Shahin, Ghada M M; Egberts, Jan-Hendrik; Pardolesi, Alessandro; Meacci, Elisa; et al. (EUROPEAN JOURNAL OF CARDIO-THORACIC SURGERY, 2018)
As the adoption of robotic procedures becomes more widespread, additional risk related to the learning curve can be expected. This article reports the results of a Delphi process to define procedures to optimize robotic training of thoracic surgeons and to promote safe performance of established robotic interventions as, for example, lung cancer and thymoma surgery. In June 2016, a working panel was spontaneously created by members of the European Society of Thoracic Surgeons (ESTS) and European Association for Cardio-Thoracic Surgery (EACTS) with a specialist interest in robotic thoracic surgery and/or surgical training. An e-consensus-finding exercise using the Delphi methodology was applied requiring 80% agreement to reach consensus on each question. Repeated iterations of anonymous voting continued over 3 rounds. Agreement was reached on many points: a standardized robotic training curriculum for robotic thoracic surgery should be divided into clearly defined sections as a staged learning pathway; the basic robotic curriculum should include a baseline evaluation, an e-learning module, a simulation-based training (including virtual reality simulation, Dry lab and Wet lab) and a robotic theatre (bedside) observation. Advanced robotic training should include e-learning on index procedures (right upper lobe) with video demonstration, access to video library of robotic procedures, simulation training, modular console training to index procedure, transition to full-procedure training with a proctor and final evaluation of the submitted video to certified independent examiners. Agreement was reached on a large number of questions to optimize and standardize training and education of thoracic surgeons in robotic activity. The production of the content of the learning material is ongoing.